Fatigue life estimation of Francis turbines based on experimental strain measurements: Review of the actual data and future trends. (March 2019) - Presas, Alexandre; Luo, Yongyao; Wang, Zhengwei; Guo, Bao
Abstract: Due to the massive entrance of new renewable energies such as wind or solar, hydraulic turbines have to work far from its designed point and withstanding multiple transients, such as starts and stops, that shorten the useful life of the machine and cause fatigue damages. The present paper reviews the complex problem of fatigue in Francis turbines particularly focused on the experimental data available for static and dynamic stresses. For this purpose, many researches, which include different Francis turbines covering a wide range of design head and power, have been considered. The experimental stresses characteristics measured with strain gauges installed on the turbine runner and obtained from previous works have been analyzed for the different operating conditions and transient states occurring in the normal life of actual Francis units. The actual computational capabilities and techniques typically used to estimate such stresses have been discussed in detail. Potential future techniques to simplify complex strain measurements on the turbine runner, computational and statistical methods to estimate turbine stresses are reviewed in this paper. Finally, the relative damage of the different operating conditions and useful life estimation of the turbine, based on past strain measurements of the runner, are addressed. Highlights: This paper reviews the complexity of fatigue life estimation of Francis turbines in all the involved steps. Data and conclusions of different manufacturers and researchers are summarized and compared. The main characteristics of stresses have been identified and the capabilities of numerical techniques discussed. Potential future experimental and numerical techniques to simplify actual experimental measurements are shown. Existing data of relative damages has been compared. Probabilistic fatigue models in hydro turbines have been addressed.